Taking care to the patients: a qualitative evaluation of a community-based ART care program in northern Namibia - Leila Katirayi; Naemi Shoopala; Kiren Mitruka; Assegid Mengistu; Godfrey Woelk; Andrew L. Baughman; Gram Mutandi; Steven Y. Hong; Ndapewa Hamunime (BMC Health Services Research, 2022)
Abstract Background Namibia is a large sparsely populated country with a high prevalence of HIV. People living with HIV who reside in remote areas often travel long distances through tough desert terrain to access HIV care and treatment. To address this barrier, community-based antiretroviral therapy (C-BART) sites were established in Okongo (2007–2008) and Eenhana districts (2016) of northern Namibia with the goal of bringing HIV and other health services closer patients’ homes. We conducted a qualitative evaluation of the acceptability and challenges of C-BART to guide program improvement. Methods For this qualitative descriptive study, research assistants collected data (August-December 2017) through in-depth interviews with 40 patients, seven health extension workers, and 11 policy/program managers, and through four focus group discussions with healthcare workers. Interviews were audio-recorded, translated, and coded using MAXQDA v.12. Data were analyzed using thematic analysis. Results The evaluation identified five themes: community ownership, acceptance of the C-BART sites, benefits of the C-BART program for the PLHIV community and their social networks, benefits of the C-BART program to the main health facility, and challenges with the C-BART program. The C-BART program was reported as life-changing by many patients who had previously struggled to afford four-wheel drive vehicles to access care. Patients and healthcare workers perceived that the community as a whole benefited from the C-BART sites not only due to the financial pressure lifted from friends and family members previously asked to help cover expensive transportation, but also due to the perception of diminished stigmatization of people living with HIV and improved health. The C-BART sites became a source of community and social support for those accessing the sites. Healthcare workers reported greater job satisfaction and decongestion of health facilities. The challenges that they reported included delays in authorization of vehicles for transportation to C-BART sites and lack of incentives to provide services in the community. Conclusion The C-BART program can serve as a model of care to expand access to HIV care and treatment and other health services to populations in remote settings, including rural and difficult-to-reach regions. The needs of healthcare workers should also be considered for the optimal delivery of such a model.